2022
DOI: 10.12998/wjcc.v10.i21.7314
|View full text |Cite
|
Sign up to set email alerts
|

Sequential treatment of severe pneumonia with respiratory failure and its influence on respiratory mechanical parameters and hemodynamics

Abstract: BACKGROUND The pathophysiological characteristics of severe pneumonia complicated by respiratory failure comprise pulmonary parenchymal changes leading to ventilation imbalance, alveolar capillary injury, pulmonary edema, refractory hypoxemia, and reduced lung compliance. Prolonged hypoxia can cause acid-base balance disorder, peripheral circulatory failure, blood-pressure reduction, arrhythmia, and other adverse consequences. AIM To investigate sequential mechanical ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
0
1
Order By: Relevance
“…32. No.1 February, 2024 174 However, these findings inconsistent with Niu et al, (2022) 2021) study contradicted with present study which found there were no difference or improvement in O2 saturation among both control and study groups. Regarding chest assessment in studied patients, the current study illustrated that there was a significant change in more than half patients among control group related to tracheal secretion from small, thin and clear secretion on admission to abundant, sticky and cloudy secretion on the 7 th day of study.…”
Section: Discussioncontrasting
confidence: 68%
“…32. No.1 February, 2024 174 However, these findings inconsistent with Niu et al, (2022) 2021) study contradicted with present study which found there were no difference or improvement in O2 saturation among both control and study groups. Regarding chest assessment in studied patients, the current study illustrated that there was a significant change in more than half patients among control group related to tracheal secretion from small, thin and clear secretion on admission to abundant, sticky and cloudy secretion on the 7 th day of study.…”
Section: Discussioncontrasting
confidence: 68%
“…HFNC is a non-invasive oxygen delivery method that mimics the natural respiratory flow rate, resulting in continuous and stable oxygen delivery. This approach has minimal impact on patients’ normal respiratory physiology and offers several benefits, including improved oxygenation and ventilation, enhanced respiratory function, and increased respiratory capacity ( 24 , 26 ). Moreover, HFNC provides airway humidification, facilitating sputum discharge and alleviating airway obstruction symptoms.…”
Section: Discussionmentioning
confidence: 99%